Development of a Distance Training Package on the Topic of Teachers’ Competencies in Teaching Occupations and Technology for Lower Secondary Teachers in Bangkok and its vicinity - Mayukhachot, Petchpong (Ratchaphruek Journal, 2014)
The purposes of this research were to (1) develop a distance training package on the topic of teachers’ competencies in teaching occupations and technology for lower secondary teachers in Bangkok and its vicinity to meet the 80/80 efficiency criterion, (2) compare learning achievements of trainees before and after receiving training package, and (3) study the opinions of trainees on whether the training package is interesting and feasible for their implementation. The research sample comprised 47teachers who taught in Occupations and Technology Learning Area at lower Secondary Schools. Research Instruments consisted of; (1) three units of the distance training package: understanding of basic technical, appliances and home electronics repair and learning activities to develop practical skills, (2) learning achievement tests administered before and after the training, and (3) a questionnaire to assess the opinions of trainees. The statistical tests employed to verify the efficiency of the training package were the E1/E2 efficiency index and t-test. Research findings showed the training package was 81.92/84.53. The trainees significantly achieved learning progress criterion and the distance training package was interesting and feasible for teachers’ implementation.